Effect of granisetron in attenuation of hypotension following spinal anaesthesia in parturients undergoing elective caesarean section - a double blind randomized controlled trial - Lamichhane, Suraj; Koirala, Siddhartha; Singh, Satyendra Narayan (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: Spinal anaesthesia has side effects like hypotension and bradycardia, which may be induced by sympathetic blockade and Bezold-Jarisch reflex (mediated by peripheral serotonin receptor, 5-HT3 type). The objective of the study was to evaluate the effects of type 3 serotonin receptors blockade by intravenous granisetron pre-treatment in spinal induced hypotension in parturient undergoing elective caesarean section. Methods: Fifty six parturient with American Society of Anaesthesiologists Physical Status I and II undergoing elective caesarean section were assigned randomly to receive either Normal Saline (control) or Granisetron 1mg intravenously five minutes before spinal anaesthesia. Spinal anaesthesia was performed with 2.2 ml 0.5% hyperbaric bupivacaine solution and then heart rates, systolic blood pressure, diastolic blood pressure, mean arterial pressure were recorded every two and half minutes for ten minutes and then every five minutes for till end of surgery after. Hemodynamic parameters were compared with baseline in each group. Results: Change in mean, systolic and diastolic arterial pressure compared with baseline value were comparable in both the groups, but use of ephedrine as rescue vasopressor drug was significantly reduced in granisetron group. The episodes of hypotension, nausea/vomiting and shivering were comparable in both groups. Conclusions: Type 3 serotonin blockade by intravenous granisetron pre-treatment does not reduce spinal induced hypotension in parturient undergoing elective caesarean section; however there is reduction in need of rescue vasopressor.